Accumulation of rare earth elements (REEs) in Pistia stratiotes (water lettuce) and Oreochromis niloticus (tilapia) in REEs industrial wastewater system - Muhammad Nor, Muhammad Nazreen; Omar, Muhammad Nor (2016)
The wide application of rare earth elements (REEs) indicates that the demand is growing and crucial for a country’s economic sector. In 2009, Malaysia has set up a REE refining plant by establishing Lynas Advance Materials Plant (LAMP) near Kuantan Pahang. During the production and refining of REEs, the activity is susceptible in causing environmental contamination. As REEs also include metals, once it enters the environment, they are hard to be destroyed but can be changed into another form. After entering into the environment, these harmful substances have a tendency to be accumulated by plants and animals (including fish). Until to date, very little efforts have been taken in monitoring toxic wastewater discharged by Lynas after extracting REEs. However, it is postulated that the environment problem related to the rare earth elements (REEs) contamination can be solved by generating the environment friendly measures called phytoremediation through bioaccumulation especially by using aquatic plants. This assumption is based on the recent reports which used aquatic plants as biological methods for removing heavy metal content through bioaccumulation. As an example, studies conducted on treatment of industrial wastewater site using aquatic plants (Pistia stratiotes, Eichornia crassipes and Salvinia molesta) and freshwater fish (Oreochromis niloticus) found that the heavy metal content such as Pb, Cr and Cd have been accumulated in aquatic plants and fish. Due to increase applications of REEs which resulted in environmental contamination, there has been a growing interest on the study of bioaccumulation processes of REEs using aquatic plants and freshwater fish.